Dividend policy and earnings per share: empirical evidence from listed manufacturing companies in sri lanka - Mithushana, R.; Kevin, T.J. (University of Jaffna, 2019)
Dividend policy is a decision taken by the company directors about dividend payment which is distributed among shareholders of the company. Demand for the company’s shares is basically arisen from the attractive dividend policy that a particular company follows on. The decision over dividend payments by the companies is therefore an important part of corporate financial management policies. Hence the study leads to an examination of the interrelationship between the dividend policy and earnings per share based on the evidence from manufacturing companies listed in Colombo Stock Exchange. Out of 41 listed companies, 19 are considered using simple random sampling method for this study. The data was collected for the period from 2012 to 2018 and obtained from the web site of Colombo Stock Exchange. Different conclusions are made by different authors regard to the relationship between dividend policy and earnings per share in the past. Therefore the study aims to find out the relationship between dividend policy and earnings per share in the manufacturing companies listed in Colombo Stock Exchange. Dividend payout ratio, dividend per share are considered as independent variable of study. The dependent variable is earnings per share of the firm which obtained directly through the annual reports of the companies. In addition to this company age, firm size was considered as control variables in the study. To test the hypothesis of this study, simple least square regression was utilized by using EViews 8 version. The analyzed results shows that a significant negative relationship between dividend payout ratio and earnings per share. Also a significant positive relationship between dividend per share and earnings per share. Company age and firm size show there are no statistically significant relationship with earnings per share. Therefore it is concluded that dividend policy decisions are highly affected the market coverage of the firms in Sri Lankan manufacturing sector.
Keywords: Dividend policy; Dividend payout ratio; Dividend per share; Manufacturing industry; Earnings per share; Colombo stock exchange